Cyberbullying on Children - Acob, Bernel Hussein D.; Briones, Mac Edward F.; Jimenez, Zergs Gio Alexander L.; Ladrido, Jeric John T.; Lamalan, Maha J.; Sinsano, David John M.; Talib, Nazreen K.; Toledo, Candellen B. (Bumi Publikasi Nusantara, 2023)
The goal of this study is to know the perspectives of the children that have experienced cyberbullying. The results showed that the victims are aware of this problem. Upon experiencing this they were distressed and treated unfairly and the trauma they experienced was quite upsetting, leading to despair; in the worst-case scenario, some young people committed suicide as a result of the frustrations brought on by cyberbullying, and their mental health was also affected by this. The findings of this study would help children be aware of this problem.